1996
DOI: 10.1095/biolreprod54.5.980
|View full text |Cite
|
Sign up to set email alerts
|

Interphase Chromosome Arrangement in Sertoli Cells of Adult Mice1

Abstract: Sertoli cells of adult male laboratory mice were examined with a number of banding techniques and by nonradioactive in situ hybridization applying different repetitive DNA probes. All banding methods revealed the typical features of mouse Sertoli cells, i.e., a central nucleolus, usually with two chromocenters associated at diametrically opposed sides in which the centromeric regions of the chromosomes are clustered. Silver staining as well as in situ hydridization with rDNA labeled part of the chromocenters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
1
15
1
Order By: Relevance
“…2I). In Sertoli cells, KIN17 staining was concentrated in the two perinucleolar satellites in which the centromeric region of the chromosomes and the telomeric sequences of the short arms are clustered (Guttenbach et al, 1996) (Fig. 2H,K).…”
Section: Expression Of Mouse Kin17 Gene During Testicular Developmentmentioning
confidence: 99%
“…2I). In Sertoli cells, KIN17 staining was concentrated in the two perinucleolar satellites in which the centromeric region of the chromosomes and the telomeric sequences of the short arms are clustered (Guttenbach et al, 1996) (Fig. 2H,K).…”
Section: Expression Of Mouse Kin17 Gene During Testicular Developmentmentioning
confidence: 99%
“…Using vimentin IF as an SEC marker on DAPI-stained testis preparations, we found that 79% or more of Atm Ϫ/Ϫ and Atm Ϫ/Ϫ p53 Ϫ/Ϫ SEC nuclei contained four or more heterochromatin clusters of various sizes (Fig. 6d), which represents a threefold increase over the control (Table 3) and data in the literature (37,41). It appears that the chromocenter distribution in Atm-mutant SECs is reminiscent of that of immature SECs (16).…”
Section: Control C-ablmentioning
confidence: 50%
“…It appears that the chromocenter distribution in Atm-mutant SECs is reminiscent of that of immature SECs (16). In addition to SECs with multiple heterochromatin clusters, both mutants contained a reduced number of SECs with two heterochromatin clusters, which are the predominant SEC type in the adult mouse (Table 3) (37,38).…”
Section: Control C-ablmentioning
confidence: 96%
See 1 more Smart Citation
“…First, centromeres are often positioned at the periphery of nucleoli in cultured cells (Guttenbach et al, 1996;Padeken et al, 2013) and the association has been functionally linked to chromatin silencing and genome stability (Padeken et al, 2013). Second, the key centromere assembly factor CAL1 and its functional human homologue Holliday junction recognition protein (HJURP), as well as human CENP-C (CENPC), localise to both centromeres and nucleoli (Dunleavy et al, 2009;Erhardt et al, 2008;Foltz et al, 2009;Pluta and Earnshaw, 1996;Wong et al, 2007).…”
Section: Introductionmentioning
confidence: 99%